2017
DOI: 10.7717/peerj.3881
|View full text |Cite
|
Sign up to set email alerts
|

Integration of lncRNA–miRNA–mRNA reveals novel insights into oviposition regulation in honey bees

Abstract: BackgroundThe honey bee (Apis mellifera) is a highly diverse species commonly used for honey production and pollination services. The oviposition of the honey bee queen affects the development and overall performance of the colony. To investigate the ovary activation and oviposition processes on a molecular level, a genome-wide analysis of lncRNAs, miRNAs and mRNA expression in the ovaries of the queens was performed to screen for differentially expressed coding and noncoding RNAs. Further analysis identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 69 publications
0
51
0
2
Order By: Relevance
“…2016 ), the TGF-beta signaling pathway, the Wnt signaling pathway, the Hedgehog signaling pathway, the Jak-STAT signaling pathway, and the Notch signaling pathway that were shown to be involved in ovary activity ( Duncan et al. 2016 ; Chen et al. 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…2016 ), the TGF-beta signaling pathway, the Wnt signaling pathway, the Hedgehog signaling pathway, the Jak-STAT signaling pathway, and the Notch signaling pathway that were shown to be involved in ovary activity ( Duncan et al. 2016 ; Chen et al. 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Small RNAs have been confirmed to be related to a diversity of biological processes including cell proliferation and apoptosis through the post-transcriptional regulation of gene expression (Charkhpour et al, 2011;Zhang et al, 2014;Yang et al, 2017). RNA profile analyses suggested that these sRNAs were involved in biological processes associated with development and immunity of honeybees (Chen et al, 2017). The key initiator of the RNAi pathway is dsRNA, which produced by proliferation process are processed into vsiRNA duplexes by dicer-2 (Xu and Zhou, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We estimated the PCR efficiency of each gene using standard curve calculation of the four cDNA serial dilution points. Cycle threshold (Ct) values were transformed to quantities using the comparative Ct method described by Chen et al (2017). We carried out lncRNA and mRNA data normalization using the GAPDH reference gene, and miRNA data normalization using the U6 reference gene.…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%